2008
DOI: 10.1007/s00404-008-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

Superficial fascial system repair: an abdominoplasty technique to reduce local complications after caesarean delivery

Abstract: Abdominal incision complications are a major source of morbidity after caesarean delivery. Repair of the superficial fascial system may avert local complications after caesarean delivery by minimising tension to the skin and increasing the initial biomechanical strength of wound which has the potential to decrease early wound dehiscence and as a by-product correct suprapubic bulging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…There may be factors beyond the superficial dermal and epidermal skin components that hold unrecognized importance. It has been reported that in cesarian section patients repairing the superficial fascial system provides structural support to the skin and significantly increases the biomechanical strength of wound repair [30]. We did not study layers deep to the dermis in skin closure.…”
Section: Discussionmentioning
confidence: 94%
“…There may be factors beyond the superficial dermal and epidermal skin components that hold unrecognized importance. It has been reported that in cesarian section patients repairing the superficial fascial system provides structural support to the skin and significantly increases the biomechanical strength of wound repair [30]. We did not study layers deep to the dermis in skin closure.…”
Section: Discussionmentioning
confidence: 94%
“…Local fasciocutaneous flaps are preferred for vulvar reconstruction because of their characteristics in terms of thickness, reliability and low morbidity. Tension may cause wound breakdown and also contribute to a restricted range of movement with associated discomfort [5]. Local fasciocutaneous flaps with SFS repair provide excellent design flexibility and can be designed and tailored to reconstruct postablative vulvar defects with good outcomes and minimal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, their use for postablative vulvar reconstruction has been limited in the literature [4]. Superficial fascial system (SFS) repair after flap transposition may avert local wound dehiscence by minimising tension to the skin through transfer of tension from the dermis to the deeper tissues [5]. The continuity of the dermis to the SFS ensures a direct energy transfer, and the oblique and vertical orientation of the SFS septae disperses the energy in a direction perpendicular to the wound tension [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations